The link between X-efficiencies and the share prices of banks before and after M&A--Evidence from China - HU, JINGYU (2019)
This research focuses on the impact of mergers and acquisitions on the cost efficiency and stock price of China’s listed banks from 2008 to 2018,and further explores the relationship between cost efficiency and stock price. The results show that after the M&A , the cost efficiency has improved. However, M&A do not improve short-term performance to banks. Finally, the regression result shows that there is a significant negative correlation between bank cost efficiency and stock price in a period of time before and after M&A.